Natural Flavonoids Derived From Fruits Are Potential Agents Against Atherosclerosis - Li, Ruo-Lan; Wang, Ling-Yu; Liu, Shuqin; Duan, Hu-Xinyue; Zhang, Qing; Zhang, Ting; Peng, Wei; Huang, Yongliang; Wu, Chunjie (Frontiers in Nutrition, 2022)
Atherosclerosis, as a chronic inflammatory response, is one of the main causes of cardiovascular diseases. Atherosclerosis is induced by endothelial cell dysfunction, migration and proliferation of smooth muscle cells, accumulation of foam cells and inflammatory response, resulting in plaque accumulation, narrowing and hardening of the artery wall, and ultimately leading to myocardial infarction or sudden death and other serious consequences. Flavonoids are a kind of natural polyphenol compounds widely existing in fruits with various structures, mainly including flavonols, flavones, flavanones, flavanols, anthocyanins, isoflavones and chalcone, etc. Because of its potential health benefits, it is now used in supplements, cosmetics and medicines, and researchers are increasingly paying attention to its role in atherosclerosis. In this paper, we will focus on several important nodes in the development of atherosclerotic disease, including endothelial cell dysfunction, smooth muscle cell migration and proliferation, foam cell accumulation and inflammatory response. At the same time, through the classification of flavonoids from fruits, the role and potential mechanism of flavonoids in atherosclerosis were reviewed, providing a certain direction for the development of fruit flavonoids in the treatment of atherosclerosis drugs.